Rethinking the Social in Innovation and Entrepreneurship - Beniamino Callegari; Bisrat A. Misganaw; Stefania Sardo (Edward Elgar Publishing, 2022)
Offering a comprehensive classification of the analytical approaches to the social within the fields of innovation and entrepreneurship studies, this book showcases a wide variety of perspectives and a collection of theoretical analysis tackling social complexity. The editors bring together contributors who mirror the heterogeneity present in the innovation and entrepreneurship fields, aiming to spark a discussion on the pluralist and critical nature of the social dimension within research, and to examine societal transformation processes and their attending multifaceted issues. Exploring how the social is analytically understood in innovation and entrepreneurship studies, the book proposes a non-exhaustive spectrum ranging from implicit assumption to explicit conceptualization in defining methodological foundations. Discussing the social and methodological challenges involved in the integration of social dimensions, this book will be a crucial companion for innovation and entrepreneurship scholars and students. This book is also a must-read for policy-makers and practitioners involved in societal transformation processes.
Keywords: 300; Social value; Social ontology; Social innovation; Social entrepreneurship; Critical studies; Sozialwirtschaft; Entrepreneurship; Innovation